Scale characteristics and growth process of shallow water delta under different lake levels— based on Delft3D numerical simulation research - Liu, Jianning; Zhou, Dejun (Frontiers in Earth Science, 2024)
Modern bays and lakes typically develop shallow deltas dominated by rivers, with lake levels playing a significant role in their formation. However, the precise effects of lake level height on the scale and growth dynamics of these deltas remain unclear. To address this, this study employs the sedimentary numerical simulation software Delft3D to model delta development under high, medium, and low lake levels. By analyzing flow velocity distribution, sediment accumulation, and sediment thickness, the study quantitatively assesses the impact of varying lake levels on shallow deltas. The results indicate that: (1) the areal extent of the delta is inversely related to the lake level, whereas sediment thickness is directly proportional to it; (2) within the same simulation period, higher lake levels tend to produce fewer breach distributary channels, while lower levels are more conducive to forming numerous breach distributary channels; however, the impact of lake level on active distributary channels is minimal; (3) deltas consist of multiple complexes. Under high lake levels, a single complex typically exhibits a bird-foot shape, characterized by active distributary channels and mouth bars, with sediment thickness decreasing from the source. In contrast, under low lake levels, a single complex tends to have a flower shape, with active distributary channels, mouth bars, and multiple breach distributary channels, resulting in a more evenly distributed sediment thickness. This research result can provide new ideas for the comparative evolution of deltas under different lake level water levels.